Influência de fatores físicos, clínicos e psicológicos na hipoalgesia induzida pelo exercício em indivíduos com dor cervical crônica: um estudo transversal - Vivaldini, Maria (Universidade Federal de São Carlos, 2025)
To evaluate the influence of psychological, physical and clinical factors on the acute response to exercise in individuals with chronic non-specific neck pain. Methods: cross-sectional study with 100 participants (mean age 36.3 ± 14.18 years; 71 women). Participants were randomized to the neck-specific exercise group and the non-specific exercise group, and the pressure pain threshold (PPT) in the left upper trapezius and left quadriceps muscles was assessed before and after exercise. The Pain Catastrophizing Scale (PCS), Tampa Scale of Kinesiophobia (TSK), Hospital Anxiety and Depression Scale (HADS) questionnaires were applied to assess psychological factors, the Baecke Physical Activity Questionnaire (BPAQ) and sedentary behavior assessed by actigraph were used to assess physical factors, and the Neck Disability Index (NDI) and the Numeric Pain Rating Scale (NPS) were used to assess clinical factors. The data were analyzed using Multiple Linear Regression models with backward selection. Results: PPT increased in the trapezius muscle (19.41% and 6.65%) and thigh muscle (7.96% and 18.57%) after specific and nonspecific exercises, respectively. Only pain catastrophizing showed a significant association with EIH in the trapezius (β=0.242; p=0.02), explaining 5.1% of the EIH variability. None of the other predictor variables showed a significant association with EIH in any of the sites evaluated. Conclusion: in mildly disabled patients with chronic neck pain higher levels of pain catastrophizing were associated with greater EIH
Influence of physical, clinical and psychological factors on exercise-induced hypoalgesia in individuals with neck pain: a cross-sectional study
Keywords: Dor cervical; Dor crônica; Cervicalgia; Limiar de dor; Exercício terapêutico; Cinesiofobia; Catastrofização; Ansiedade; Depressão; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL